Personal Targets for Public Servants and Their Support the Governance’s Performance Conception in Russia - Elena Vasilieva; Mariia Rubtcova; Valentina Kaisarova; Alexander Kaisarov; Oleg Pavenkov (International Review of Management and Marketing, 2015)
Public servants are important actors in the system of public goods delivery. Performance measuring governance in terms of the modern state is centres on establishing the contentment of the customers purchasing these goods. This means the public servants need special professional skills for this aim: a personal performance management based on professional growth and focused on the main mission of the government—social support in mind of fulfilling civil clients’ needs. We would like to identify the degree of personal support for this conception. The research was carried out in December 2014 in the Republic of Sakha (Yakutia), Russia. In regard to sampling procedure, we utilised a quota sampling with a representative age and gender distribution. We selected 303 participants, all of whom in the position of public servants of the Republic of Sakha (Yakutia). The research method adopted was a questionnaire; data processing was carried out using SPSS. The results of the research show that public servants are still guided by old skills and requirements. Moreover, they are dedicated to the classical and old-fashioned conception of rational bureaucracy, based on M. Weber’s principles, namely administrative efficiency, power hierarchy, formally established and clearly documented system of rules, and impersonal activity and emotional neutrality relations. Thus, most public servants consider their main goal as governance (28.2%). They describe their job as the performance of the state (42%), administration (17%) and execution of orders (17%). However, staff at the age of 30 years (35%) more frequently chooses the satisfaction of client needs and the delivery of public goods as the main goals of authorities. This gives us hope that, in the next five years, the professional skills of public servants will change in line with new requirements if the educational policy remains the same.